2014
DOI: 10.1002/pro.2557
|View full text |Cite
|
Sign up to set email alerts
|

Protected hinge in the immunoglobulin G2‐A2 disulfide isoform

Abstract: Human IgG2 consists of disulfide-mediated structural isoforms, classified by the number of Fab arms disulfide-linked to the heavy chain hinge. In the IgG2-B isoform, both Fab arms are linked to the hinge region, and in IgG2-A, neither Fab arm are linked to the hinge. IgG2-A/B is a hybrid between these two forms, with only one Fab arm disulfide-linked to the hinge. Within each of these isoform types are subtypes, with subtle disulfide-linkage differences. Here we explored the structural basis for the A 1 and A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…40 Literature reported IgG 2 κ to vary between A1, A2, B, and A/B isoforms, favoring the A/B and B isoforms. 37,41 As expected, the majority of our product was in the A/B and B isoforms, and consisted over 60% of total product as determined by RP-HPLC (data not shown).…”
Section: Trisulfide Detection In An Igg 2 κsupporting
confidence: 80%
See 1 more Smart Citation
“…40 Literature reported IgG 2 κ to vary between A1, A2, B, and A/B isoforms, favoring the A/B and B isoforms. 37,41 As expected, the majority of our product was in the A/B and B isoforms, and consisted over 60% of total product as determined by RP-HPLC (data not shown).…”
Section: Trisulfide Detection In An Igg 2 κsupporting
confidence: 80%
“…Pritatsky et al reported trisulfides in IgG 2 hinge region, but their tested antibody was an IgG 2 λ and the majority of their product was in the A isoform . Literature reported IgG 2 κ to vary between A1, A2, B, and A/B isoforms, favoring the A/B and B isoforms . As expected, the majority of our product was in the A/B and B isoforms, and consisted over 60% of total product as determined by RP‐HPLC (data not shown).…”
Section: Resultssupporting
confidence: 61%
“…By nonreducing peptide mapping and Edman sequencing even more disulfide subvariants of the IgG2‐A/B and IgG2‐B structures could be identified . IgG2‐A1 and IgG2‐A2 isoforms with slight differences in disulfide linkages are also described elsewhere . A2 was more resistant to reduction and had a lower Fc glycan flexibility.…”
Section: Disulfide‐ and Hinge‐related Modificationsmentioning
confidence: 92%
“… 30 The A’ species has the same disulfide configuration as the A-form, but contains a hinge disulfide that is protected from reduction. 39
Figure 2. nrRP-UHPLC chromatograms of the starting material (A), redox-enriched A and B isoforms (B), and CEX-fractionated IgG2-A and IgG2-B mAbs (C).
…”
Section: Resultsmentioning
confidence: 99%